Entrepreneurship Education in Indonesia: What is Known? A Systematic Literature Review of Trends, Focus, and Research Agenda - Anggi Saputra; Suci Alifah Rahmandani; Yudesia Ririn Haryati; Armiati Armiati; Susi Evanita (Universitas Negeri Padang, 2026)
Entrepreneurship education should be understood not only as a means of building a business, but also as a transformative educational process. Therefore, this systematic review aims to examine entrepreneurship education in Indonesia: What is currently known? A systematic literature review of trends, research focuses, and research agendas. This paper adopts a systematic literature review in the ScienceDirect and Semantic Scholar databases from 2021 to 2026, using the Preferred Reporting Items for Systematic Reviews and Meta-analyses (PRISMA). Based on predetermined inclusion criteria, a total of 16 articles published between 2021 and 2026 were analyzed in-depth and systematically. This is because only 16 articles from that period aligned with the scope of this study on entrepreneurship education. The review’s findings indicate that entrepreneurship education plays a central role in shaping entrepreneurial competencies, intentions, and behaviors among students at various educational levels. The research findings confirm that experience-based pedagogical approaches, institutional support, and the integration of digital technology are key factors in enhancing the effectiveness of entrepreneurship education. This study is expected to contribute to fostering entrepreneurial intentions in developing competencies, innovative mindsets, and creating economic value in entrepreneurship education in Indonesia in the long term.